Influence of Gender Diversity, Age, Education, and Work Experience Top Management Team on Intellectual Capital Performance: Empirical Study on Sector Companies Banking in 2021-2022 - Humairo, Syiva; Abidin, Zaenal (Journal of Business Management and Economic Development, 2024)
The aim of this research is to analyze the influence of Gender Diversity, Age, Education and Work Experience on Intellectual Capital Performance. The sample used in this research consisted of 23 companies selected using purposive sampling. This research uses quantitative methods and the research object is banking companies listed on the Indonesian Stock Exchange for the 2021-2022 period. The research method used is Common Effect Model (CEM) panel data which is processed using the Eviews version 12 application. The data used is in the form of annual reports and financial reports for the period 2021-2022. This research uses multiple regression analysis. The variables in this research are Disclosure of Intellectual Capital (Y), Gender Diversity of the Female Top Management Team (X1), Age of the Top Management Team (X2), Education of the Top Management Team (X3) and Work Experience of the Top Management Team (X4). The results of the statistical analysis show that partially the Gender Diversity Top Management Team Female variable has a positive and insignificant effect on Intellectual Capital Performance. The age of the Top Management Team has a negative and significant effect on Intellectual Capital Performance. Then, Top Management Team education has a positive and insignificant effect on Intellectual Capital Performance. Lastly, Top Management Team experience has a negative and insignificant effect on Intellectual Capital Performance.